PENGARUH RELAKSASI PROGRESIF TERHADAP TINGKAT KECEMASAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA DAERAH SURAKARTA - Dwi Ari, Purwaningtyas Lisa; Pratiwi, Arum (Universitas Muhammadiyah Surakarta, 2010)
Schizophrenia which is an mental disorder persistent and serious to resulting behavior of psychotic, concrete idea and difficulty in process of information, the relation of interpersonal and solves problem. Patient schizophrenia often shows behavior to withdrawl, isolated, difficult to be arranged and worried. Therapy applied for patient schizophrenia experiencing anxiety of them is with behavior therapy. Progressive relaxation practice as one of techniques of relaxation of muscle has proven in therapy program to stress of muscle can overcome sigh anxieties, insomnia, fatigue, muscle cramps, neck pain in bone and waist, high blood pressure, muttering and light phobia. Purpose of this research is to know progressive relaxation technique influence to level of anxiety at client schizophrenia in Area Mental Hospital Surakarta. This research method is experiment or quasi experimental with pretest and posttest with control group design, this research applies two groups,which is the one group is given treatment and the other one groups as control. The research sample is 30 respondens with proportional technique of random sampling. Data processing technique applies test analytical technique Mann Whitney U-test. The result this research are indicates that: the level of anxiety of patient schizophrenia in RSJD Surakarta before therapy giving or pre test at group of experiment most of light (73%) while at group of control most of also light (80%), the level of anxiety of patient schizophrenia in RSJD Surakarta after therapy giving of post test at group of experiment entirely light (100%) while at group of control most of still be light (87%) but still there is being (13%), and there is progressive relaxation influence to level of anxiety of patient schizophrenia in RSJD Surakarta.